Handling, Reproducing and Cryopreserving Five European Sea Urchins (Echinodermata, Klein, 1778) for Biodiversity Conservation Purposes - Estefanía Paredes; Sara Campos; Alba Lago; Tracy Bueno; Julien Constensoux; Damian Costas (Animals, 2022)
In this work, five local sea urchin species found in European waters were studied. Four were regular species: Sphaerechinus granularis, Psammechinus miliaris, Echinus esculentus (Linnaeus, 1758) and the edible sea urchin Paracentrotus lividus; and one was an irregular species, Echinocardium cordatum. These five species of sea urchins have been studied regarding their fertility, toxicity of cryoprotecting agents, cryopreservation of different cell types and chilling injury. The baseline fertility is similar in P. lividus, P. miliaris and S. granularis. Nonetheless, the sperm:egg ratio, contact time and development of the fertilization envelope would need to be studied further on a case-by-case basis. Sperm can be maintained inactively in the gonad (4 °C), and oocytes also maintain quality in sea water (4 °C), even after 72 h. Sperm was cryopreserved for four species with some post-thaw intra specific variability, and embryo cryopreservation was only possible for S. granularis. Overall, this study provided a wider vision of the biology and reproduction of these species that will help us develop tools for their biodiversity conservation through cryopreservation.